'Something from nothing'—constructing Israeli rurality. (3rd October 2019) - Rosenberg, Elissa
Abstract: This paper analyses the debates regarding native versus non-native plantings in the Israeli kibbutz and their role in the reinvention of the Israeli rural landscape. Based on the assumption that the representation of landscape is always tied to larger questions concerning culture and identity, the genesis of the landscape that has by now become fully naturalised as the new local rural landscape is examined through an analysis of the cultural and ideological roots of its planting design. The Israeli debates reflected the paradox at the heart of a culture that sought to be both 'new' and 'native.' The ethos of 'something from nothing'—expressed as the creation of a new green landscape ex nihilo —as well as the advocates for the use of native plants, will be examined in relation to their respective constructions of a landscape narrative.